Nursing and rehabilitation of the patient with the cervical spine injury. Case study - Kołpa, Małgorzata; Grochowska, Aneta (Nursing in the 21st Century, 2014)
NURSING AND REHABILITATION OF THE PATIENT WITH THE CERVICAL SPINE INJURY. CASE STUDY Introduction. Quick pace of life, recklessness and lack of prudence frequently lead to tragic accidents consequently affecting further quality of life of the patient and his/her family. The importance of the problem is incommensurately increasing and it is more complex regarding the height of the injury. The higher level of the spinal injury, the greater influence of the spinal cord injury on further physical and mental fitness of the patient. The cervical spine injury leads to long-lasting and irreversible changes in functioning of the whole body. The vast extent of disorders imposes multi-complex character of the actions undertaken as early as during the first moments following the sustained injury. The main goal should be to reach the spinal cord decompression as soon as possible. Undertaken surgical or conservative procedures constitute only the beginning of the long-term process aiming at restoring the lost functions. This can only be achieved by regular and long-lasting medical nursing and rehabilitation process with complete involvement of the whole interdisciplinary team and the patient himself/herself, his/her motivation, attitude and willingness to cooperate. Aim. The objective of the thesis was to present the complete process of treatment and rehabilitation of the patient with the cervical spine injury. This work also demonstrates the evaluation of efficiency and effectiveness of undertaken medical actions.